idenification of nursing activities at medical and surgical nursing units in Vietnam - Minh, Nguyen Thi Hong (The Graduate School, Ajou University, 2011)
Abstract The purpose of this research is: to explore nursing activities performed by Vietnamese nurses; to identify time of each nursing activity that is performed by medical and surgical nurses and proportion of direct and indirect nursing time; to identify the job independence level of each nursing activity. The sample consisted of 201 nurses working in two hospitals in Vietnam. The instrument used to collect data from two hospitals was a questionnaire including 145 nursing activities, which was developed by the Korean nurses and modified by the leader group of Vietnamese nurses. Each nursing activity was described for time, frequency and job independence level. The 120 nursing activities were performed by the medical nurses and 123 nursing activities were performed by the surgical nurses. Average time of each nursing activity, in which the nurses spend the most time, is 31.1 minutes for transfusion and the lowest time is 0.5 minute for respiratory pattern measurement or body weight measurement. Average frequency of each nursing activity, which the nurses performed most commonly at both units are blood pressure check, pulse check, monitoring, and medication management. The lowest frequency for the activity performed by the Vietnamese nurses is the complete isolation for infection prevention and tube feeding via gastrostomy. The highest percentage for direct nursing time is of safety with 25.1% and 31.5% respectively for day and night shift at medical nursing unit. The 27.1% and 28.1% respectively is of safety for day shift and night shift at surgical nursing unit. The lowest percentage is of hygiene with 0.9% for day shift at medical nursing unit. Also, 0% is of communication and assistance during night shift at surgical nursing unit. The highest percentage for indirect nursing time is of recording with 58.9% at surgical nursing unit and 49.7% at medical nursing unit for day shift. The total of nursing time is 68.6% (3.62 hours) and 31.4% (1.65 hours) for direct and indirect nursing activities respectively for the day shift in the medical nursing unit. The 69.6% (3.04 hours) and 40.5% (2.07 hours) are the direct and indirect nursing time respectively for day shift by a nurse at the surgical nursing unit. IDENTIFICATION OF NURSING ACTIVITIES 2 The total of nursing time is 70.8% (4.19 hours) and 29.2% (1.72 hours) for direct and indirect nursing activities respectively for the night shift in medical nursing unit. The 57.9% (3.67 hours) and 42.1% (2.67 hours) are the direct and indirect nursing time respectively for night shift by a nurse at the surgical nursing unit. The 71 nursing activities were identified to be completely independent and none of the nursing activity was completely dependent. This study adds to describe the current situation in Vietnamese Hospitals. Overall, the direct nursing time is higher than the indirect nursing time in both units. The percentage of direct nursing activities at medical unit is higher than at the surgical nursing unit, which is used to build up the nursing cost. Much time is spent for indirect nursing activities at surgical nursing unit calculated 40.5% for day shift and 42.1% for night shift, in which the nurse spend for recording is very high and needs to be controlled. The percentage of spiritual support and communication, which involves admission interview, consulting, personal education, religious support and communication, is very low and it needs to be improved through proper nursing education.
학위논문(석사)--아주대학교 일반대학원 :간호학과,2011. 2
Keywords: nursing activities; medical; surgical nursing